The structure and distribution of glandular trichomes on the stems and leaves of drug eyebright (Euphrasia stricta D. Wolff ex J. F. Lehm.) - Elżbieta Weryszko-Chmielewska; Anna Matysik-Woźniak; Dagmara Sadowska (Acta Agrobotanica, 2012)
Euphrasia stricta is a medicinal plant being one of the ingredients of "Herba Euphrasiae". Many studies have been devoted to the identification of biologically active substances in the herb of eyebright, but much less research has been done on the constitution of glandular structures of this taxon. This paper relates to glandular trichomes located on the stems and leaves of E. stricta. The trichome structure was examined using light and scanning electron microscopy. It was shown that the stems of E. stricta were mainly covered by non-glandular trichomes, whereas glandular trichomes were rarely found on them. However, clusters of short capitate trichomes were found to occur in specific epidermal regions on both surfaces of the leaf blades and bracts. On the adaxial leaf surface, glandular trichomes grew only in the grooves above the vascular bundles, while on the abaxial surface in the depressions located in the expanded part of the teeth. The glandular hairs consisted of 1-2 cells of the stalk and a two-celled head. Trichomes with 3- or 4-celled heads were found sporadically. The glandular trichomes functioned non-synchronously, since they differed in head size and the colour of cell protoplasts. The presence of a light secretion was found on the surface and around the trichomes in both fresh and dry plant material.